Adsorption of genetically engineered proteins studied by time‐of‐flight secondary ion mass spectrometry (TOF‐SIMS). Part A: data acquisition and principal component analysis (PCA) - Suzuki, Noriaki; Gamble, Lara; Tamerler, Candan; Sarikaya, Mehmet; Castner, David G.; Ohuchi, Fumio S. (Wiley, 2007)
Abstract Recent progress in the adaptation of combinatorial biology selection protocols to materials science has created a new class of polypeptides with specific affinity to inorganics. Here, we use one of the genetically engineered proteins, a gold binding protein (GBP‐1), to assess quantitatively its binding specificity to Au, Ag and Pd surfaces by using time‐of‐flight secondary ion mass spectroscopy (TOF‐SIMS). The GBP‐1, originally selected using cell‐surface display techniques, consisting of 14 amino acids with a sequence of MHGKTQATSGTIQS, was used in this study. Three‐repeat and single‐repeat forms of GBP‐1 were prepared. In earlier studies, GBP‐1 was shown to bind to Au particles and self‐assemble on flat Au surfaces. Through the fingerprint analysis of these specific peptides, their role in binding can be investigated in terms of their contribution to surface interaction possibly forming the right molecular architecture for binding. To achieve this purpose, a large‐sized data matrix produced by TOF‐SIMS must be properly treated for analysis. In Part A, we use principal component analysis (PCA) to visualize the spectral variations for a variety of adsorption conditions and suggest possible contribution of the specific types of amino acids (binding site) to the interactions. Copyright © 2007 John Wiley & Sons, Ltd.